Effect of dasatinib on EMT-mediated-mechanism of resistance against EGFR inhibitors in lung cancer cells. (February 2017) - Sesumi, Yuichi; Suda, Kenichi; Mizuuchi, Hiroshi; Kobayashi, Yoshihisa; Sato, Katsuaki; Chiba, Masato; Shimoji, Masaki; Tomizawa, Kenji; Takemoto, Toshiki; Mitsudomi, Tetsuya
Highlights: A Combination of erlotinib and dasatinib prevented the acquired resistance via EMT. The acquired resistance mechanism of the combination therapy was T790 M mutation. Preemptive combination therapy may be a promising strategy. Abstract: Objective: The epithelial to mesenchymal transition (EMT) is associated with acquired resistance to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in certain non-small cell lung cancers that harbor EGFR mutations. Because no currently available drugs specifically kill cancer cells via EMT, novel treatment strategies that overcome or prevent EMT are needed. A recent report suggested that dasatinib (an ABL/Src kinase inhibitor) inhibits EMT induced by transforming growth factor (TGF)-beta in lung cancer cells (Wilson et al., 2014). In this study, we analyzed effects of dasatinib on the resistance mechanism in HCC4006 cells, which tend to acquire resistance to EGFR-TKIs via EMT. Materials and methods: Sensitivity to dasatinib in HCC4006 and HCC4006 erlotinib-resistant (ER) cells with an EMT phenotype was analyzed. HCC4006 cells acquired resistance against the combination of erlotinib and dasatinib (HCC4006EDR) following chronic treatment with these drugs. The expression of EMT markers and the resistance mechanism were analyzed. Results: Short-term or long-term treatment with dasatinib did not reverse EMT in HCC4006ER. In contrast, HCC4006EDR cells maintained an epithelial phenotype, and the mechanism underlying resistance to erlotinib plus dasatinib combination therapy was attributable to a T790M secondary mutation. HCC4006EDR cells, but not HCC4006ER cells, were highly sensitive to a third-generation EGFR-TKI, osimertinib. Conclusions: Although dasatinib monotherapy did not reverse EMT in HCC4006ER cells, preemptive combination treatment with erlotinib and dasatinib prevented the emergence of acquired resistance via EMT, and led to the emergence of T790M. Our results indicate that preemptive combination therapy may be a promising strategy to prevent the emergence of EMT-mediated resistance.